ARMENIA’S DOMESTIC POLICY AFTER THE VELVET REVOLUTION: SELECTED ISSUES - MIARKA, Agnieszka (CENTRAL ASIA AND THE CAUCASUS, 2024)
The article aims to analyze and characterize changes in Armenia’s domestic policy initiated by the reform government led by Prime Minister Nikol Pashinyan. In the course of research, the emphasis was placed on the presentation of such issues as the fight against corruption, the reform of the tax system, the fight against poverty and the reform of the judiciary system. It was also extremely important to present the short-term implications of the implemented measures and to discuss the attitude of the society towards the executed reforms, as well as public support for the operations of new political forces.In the light of the results of the re- search, it is clear that the activity of the post- revolutionary government has significantly changed the domestic policy vector of Armenia, bringing the country closer to meeting international democratic standards and strengthening the economic sector.